Transformational Leadership, Affective Commitment, And Mediating-Analysis of Individual’s Work Performance Moderated by Personal Characteristic; Work Duration - Indradewa, Rhian; Fernando, Raymon; Napitupulu; Purwanto; lasniroha Sarumpaet, Tetty (International Journal of Psychosocial Rehabilitation, 2020)
Transformational leadership plays role in improving individual’s work performance by the influences of an ideal leader, inspirational motivation, intellectual stimulation, and individual consideration, either directly or indirectly. In addition, it is also influenced by either direct or indirect affective commitment. The aim of this study is to investigate the effect of the transformational leadership on the individual’s work performance mediated by affective commitment and moderated by personal characteristic; work duration, both partially and simultaneously. The respondent participated in this study is a group of people who work as production operator in a manufacturer in Tangerang, Banten, Indonesia. The questionnaire was distributed to the respondents and finally obtained 200 samples. The analysis process in this study applied the Structural Equation Model. The result of this study shows that the individual’s work performance is affected by the affective commitment. In addition, the employee’s emotional bonding has grown as the result of the effect of the leadership style and organization that are able to build their trust. The management is able to make the employees feel appreciated, and they are also involved in the organization by giving positive motivation to achieve the organization’s vision and mission.